The Impact of Work Environment and Work Stress toward Turnover Intention at Discovery Kartika Plaza Hotel Bali - Guna Saputra, I Gede Made Indra; Santi Diwyarthi, Ni Desak Made; Jata, I Wayan (Jurnal Multidisiplin West Science, 2024)
The aim of this study is to determine how the work environment and work stress impact turnover intention. The study was conducted at Discovery Kartika Plaza Hotel Bali, with a sample of 79 respondents. Slovin's formula and stratified random sampling were used to collect the sample. Data were gathered through questionnaires distributed to all employees of Discovery Kartika Plaza Hotel. Data analysis was carried out using multiple linear regression analysis, classical assumption tests, t-tests, F-tests, and the coefficient of determination. All these techniques were processed using SPSS version 26 for Windows. The results showed that the work environment variable (X1) and the work stress variable (X2) had a positive and significant partial effect on turnover intention, with a calculated t-value greater than the t-table value, namely 3.243, which is greater than 1.665, and a significance value α = 0.002 < 0.05. This study indicates that the work environment (X1) and work stress variable (X2) have a positive partial and simultaneous effect on employees' turnover intention at Discovery Kartika Plaza Hotel Bali. In other words, the worse the work environment and the higher the work stress, the greater the employees' desire to leave the hotel. Hotel management should pay attention to the quality of their work environment and strive to reduce existing stress in the workplace.